2021
DOI: 10.21926/jept.2102019
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Metal Anode for High-Power and High-Capacity Rechargeable Batteries

Abstract: Because lithium metal exhibits high specific capacity and low potential, it is the best candidate for fabricating anodes for batteries. Rechargeable batteries fabricated using lithium anode exhibit high capacity and high potential cathode; these can be potentially used to fabricate high energy density batteries (>500 Wh kg–1) that can be used for the development of next-generation electric vehicles. However, the formation and growth of lithium dendrites and the low coulombic efficiency recorded during lithi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…The CE for lithium deposition and stripping of the Li/1 m LiPF 6 in EC‐DMC (1 : 1 v/v)/Cu cell at 0.5 mA cm −2 was reported to be as low as 88.7% [29] . The retention of the electrolyte after 10 cycles at CE of 0.887 is around 30 % [30] . The KW separator was thus not effective to suppress lithium dendrite formation and growth at high current density with the carbonate based electrolytes.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The CE for lithium deposition and stripping of the Li/1 m LiPF 6 in EC‐DMC (1 : 1 v/v)/Cu cell at 0.5 mA cm −2 was reported to be as low as 88.7% [29] . The retention of the electrolyte after 10 cycles at CE of 0.887 is around 30 % [30] . The KW separator was thus not effective to suppress lithium dendrite formation and growth at high current density with the carbonate based electrolytes.…”
Section: Resultsmentioning
confidence: 95%
“…[29] The retention of the electrolyte after 10 cycles at CE of 0.887 is around 30 %. [30] The KW separator was thus not effective to suppress lithium dendrite formation and growth at high current ChemElectroChem density with the carbonate based electrolytes. Therefore, an electrolyte with a high CE should be selected.…”
Section: Cycle Performance Of Li/1 M Lipf 6 In Ec-dec (1 : 1 V/v)/li ...mentioning
confidence: 99%
“…The reason for this is the formation and growth of lithium dendrite when a rechargeable battery with a lithium anode is operated for longer cycling periods at a high current density [18]. In order to resolve this issue, modified lithium/electrolyte systems that prevent the formation and growth of lithium dendrite [19,20] have been proposed. In this context, the present study proposes aqueous lithium-air batteries with a 4.5 M LiFSI in DME electrolyte and a mixed separator comprising KW and PP for the anode side electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to remaining stable when in contact with lithium metal, the interlayer electrolyte also requires preventing the formation of lithium dendrites during the lithium deposition at high current density. Several studies have reported the formation and growth of lithium dendrites when using non-aqueous electrolytes [18][19][20][21][22]. However, Zhang and co-workers reported an electrolyte that did not result in the formation of lithium dendrites even at a high current density; the authors reported that the cell comprised a Li/4 M lithium bis(fluorosulfonyl)imide (LiFSI) in 1,2 dimethyloxyethane (DME)/Li and could be cycled at 10 mA cm -2 over a period of 0.1 h for >6,000 cycles [21].…”
Section: Introductionmentioning
confidence: 99%